Cultural-Artistic Value in Epic and Festival of the Muong Thanh Hoa People - Vu Thi Dung, (International Journal of Humanities and Education Development (IJHED), 2022)
The epic The Land of the Earth is a system of mythical stories about the formation of heaven and earth of the Muong. It is also considered history and an encyclopedia of the customs of the Muong people. This epic is both pride and respect in the cultural life of the Muong community. This article studies several outstanding cultural symbols of the epic "Land for the Land" which have been preserved and remained quite intact in the Poon Poong festival - one of the most important festivals of the Muong people in Thanh Hoa.